2015
DOI: 10.1586/1744666x.2015.1052409
|View full text |Cite
|
Sign up to set email alerts
|

Venom immunotherapy: clinical efficacy, safety and contraindications

Abstract: Venom-specific immunotherapy (VIT) is considered for the treatment of patients with IgE-mediated systemic allergic reactions (SARs) after developing a Hymenoptera venom allergy. Tolerance is achieved in a majority of patients after only a few days or even hours of rush immunotherapy. After VIT discontinuation, the allergy returns in up to 15% of patients. During VIT, the majority of patients have local reactions at the site of venom injections. SARs to VIT are much more frequent in honeybee-treated patients th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 59 publications
0
10
0
1
Order By: Relevance
“…Moreover, some promising findings suggested that HBV can be used in combination with standard chemotherapy, e.g., cisplatin 26 , 27 . Another important application of HBV is venom immunotherapy, which is an effective treatment of severe honeybee sting-induced allergic reactions 28 . We have gained knowledge of the mechanism of action of selected HBV compounds 19 , 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some promising findings suggested that HBV can be used in combination with standard chemotherapy, e.g., cisplatin 26 , 27 . Another important application of HBV is venom immunotherapy, which is an effective treatment of severe honeybee sting-induced allergic reactions 28 . We have gained knowledge of the mechanism of action of selected HBV compounds 19 , 29 .…”
Section: Introductionmentioning
confidence: 99%
“…VIT is overall effective in protecting at further stings those subjects with HVA, as confirmed by numerous trials , 5 , 9 , 15, 16, 17 where different extract preparations were employed. The occurrence of local (even systemic) reactions still represents one of the main concerns, expecially with Honeybee-VIT.…”
Section: Discussionmentioning
confidence: 71%
“…Potrzeba użycia adrenaliny z powodu NDS może dotyczyć 0,2-5,0% chorych poddawanych VIT [23]. Do istotnych czynników zwiększających ryzyko wystąpienia NDS w trakcie VIT należą: faza dawek wzrastających i rodzaj użytego schematu, starszy wiek (głównie z powodu chorób sercowo-naczyniowych), mastocytoza lub duże wyjściowe stężenie tryptazy [23][24][25][26]. Dlatego też przed VIT z jadem pszczoły zaleca się ocenę aktywacji bazofilów na alergen (BAT, odsetek bazofilów CD 63+) w celu identyfikacji chorego z dużym ryzykiem rozwoju ciężkich NDS [25].…”
Section: Bezpieczeństwo Immunoterapii Alergenowej W Alergii Na Jad Owunclassified